Quality of life in patients with Ankylosing Spondylitis in Duhok government, Kurdistan of Iraq - Nahida Zuber Ali; Muhammed Tahir Rasool (Advanced Medical Journal)
Background and objectives: Spondylarthritis is a broad spectrum of chronic inflammatory diseases, and one of its of phenotypes is ankylosing spondylitis. Ankylosing spondylitis can impact the quality of life and health status because of pain, fatigue, and stiffness. This study aims to evaluate health-related quality of life and extra-articular manifestation in patients with ankylosing spondylitis in Iraq /Duhok city.